Ex Ante Litigation Risk and Audit Firm Hiring and Retention - Docimo, William M.; Xu, Nina (The Accounting Review, 2026)
ABSTRACT This study examines the impact of ex ante litigation risk on auditor hiring and retention. Using employee data from LinkedIn, we find ex ante accounting-related litigation risk is associated with fewer auditors joining and more auditors leaving an audit office, whereas we fail to find any impact of nonaccounting litigation risk. Moreover, ex ante accounting-related litigation risk is associated with audit firms' hiring less experienced and less educated auditors, suggesting ex ante litigation risk impacts the quality of auditing hires. We also find that the impact of ex ante litigation risk is concentrated in audit offices with more outside job opportunities and in those that are more susceptible to changes in litigation risk. Our results highlight the impact of ex ante litigation risk on audit labor supply, providing insights concerning the unintended consequences of increasing auditors' legal liability. Data Availability: All data used in this study are based on publicly available information obtained through the services or authors cited in the manuscript. JEL Classifications: M42.